Engaging EFL Junior Students in Collaborative Online Audio of Narrative Texts in Learning Extensive Listening: A Classroom Action Research - Windi Widiawati; Elih Sutisna Yanto; Abdul Kodir Al-Baekani (Journal of Educational Sciences, 2026)
Listening comprehension remains a significant challenge for many Indonesian junior high school EFL students, primarily due to limited exposure to and insufficient engagement with authentic listening materials. This Classroom Action Research explores the effectiveness of using collaborative online audio podcasts featuring narrative texts to enhance extensive listening skills and increase student engagement. The study, conducted over five sessions with eighth-grade students, utilized qualitative methods including classroom observations, reflective journals, and semi-structured interviews. The findings indicate that podcast-based collaborative listening activities significantly boosted students' motivation, participation, and comprehension of narrative texts. Students reported enjoying the interactive and social aspects of group listening tasks, which fostered active discussions and peer support, consistent with Vygotsky’s Sociocultural Theory and Mayer’s Cognitive Theory of Multimedia Learning. Despite some challenges, such as difficulties with vocabulary and fast speech, the overall impact on listening skills and student attitudes was positive. This study suggests that integrating podcasts into collaborative extensive listening practices provides a practical, engaging, and effective approach to improving EFL listening comprehension in junior high school settings.